Transboundary Fisheries Management under Implementation Uncertainty - Marita Laukkanen (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper examines how non-binding co-operative agreements on marine fisheries management can be sustained when management plans in participating countries are implemented with error. The effects of implementation uncertainty on voluntary co-operation are compared to those of recruitment uncertainty. A self-enforcing co-operative solution can only be sustained when uncertainty is not too pronounced. Even when a co-operative agreement can be achieved, frequent phases of reversion to non-co-operative harvest levels are needed to support the agreement. The implications of recruitment uncertainty for implicit co-operation are less detrimental than those of implementation uncertainty.
Keywords: Q22; C72; 330; Fisheries management; Transboundary fisheries; Non-cooperative games; Implementation uncertainty; Fischerei; Bioökonomik; Internationale Zusammenarbeit; Theorie